The Child Protection Register: A tool in the accident and emergency department?. Issue 3 (1st May 2002) - Flanagan, N M; MacLeod, C; Jenkins, M G; Wylie, R
Abstract : Aims: To determine the number of children on the Child Protection Register (CPR) attending the accident and emergency (A&E) department and the referral source, diagnostic category, and frequency distribution for such attendances. To determine whether lack of knowledge that a child is on the CPR results in failure to suspect non-accidental injury (NAI) if the standard indicators of NAI have been sought. Methods: Access to the CPR was obtained. Records of each child attending the A&E departments of the United Hospitals Trust between June 1994 and May 2000 were reviewed. Results: Over the six years 191 children were on the CPR. Seventy nine (41%) attended A&E departments on 206 occasions. Frequency of attendance ranged to 18 with a mean of 2.6. Self referral was the commonest source of referral (81%) followed by general practitioners (13%), 999 calls (5%), and a small number from schools (1%). Most presentations involved trauma—upper limb (21%), lower limb (14%), and head injury (8%). Almost all cases of trauma were adjudged to be consistent with the history and NAI not suspected. Common childhood illnesses accounted for the remainder of presentations. Only six children were identified as being on the CPR at the time of presentation. Concerns were raised in two other cases and concerns should have been raised in three other children. Social Services were alerted on five occasions directly by the parents themselves. Conclusions: It is concluded that in the absence of knowledge of the status of a child on the CPR attending the A&E department, that screening for the standard indicators of NAI is adequate to detect most cases of NAI.